2012
DOI: 10.1038/leu.2011.376
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin modifications induced by the AML1-ETO fusion protein reversibly silence its genomic targets through AML1 and Sp1 binding motifs

Abstract: The AML1-ETO fusion protein, which is present in 10 --15% of cases of acute myeloid leukemia, is known to repress myeloid differentiation genes through DNA binding and recruitment of chromatin-modifying proteins and transcription factors in target genes. ChIP-chip analysis of human hematopoietic stem/progenitor cells transduced with the AML1-ETO fusion gene enabled us to identify 1168 AML1-ETO target genes, 103 of which were co-occupied by histone deacetylase 1 (HDAC1) and had lost the hyperacetylation mark at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 44 publications
(52 reference statements)
1
29
1
Order By: Relevance
“…In a recent study, chromatin immunoprecipitation chip analysis of human hematopoietic stem/progenitor cells transduced with the AML1-ETO fusion gene resulted in the identification of 1168 AML1-ETO target genes, 103 of which were co-occupied by HDAC1 and had lost the hyperacetylation marks on histone H4 at Lys5, Lys8, Lys12, Lys16 and 264 of which showed induction of trimethylation at Lys9 of histone H3 (H3K9me3). In the presence of these epigenetic modifications, enrichment of genes involved in hematopoietic differentiation and in specific signaling pathways was observed; this was associated with an 'inactive' chromatin status, so AML1-ETO binding correlates with changes in the histone modification pattern and increased association of HDACs [47]. On the other hand, AML1-ETO can interact, via its Nervy homology region (which is involved in oligomerization of ETO), with the histone acetyltransferase p300, which acetylates lysines of histones in its target genes, thus activating gene transcription [48].…”
Section: Aml1-eto/t(8;21)mentioning
confidence: 99%
“…In a recent study, chromatin immunoprecipitation chip analysis of human hematopoietic stem/progenitor cells transduced with the AML1-ETO fusion gene resulted in the identification of 1168 AML1-ETO target genes, 103 of which were co-occupied by HDAC1 and had lost the hyperacetylation marks on histone H4 at Lys5, Lys8, Lys12, Lys16 and 264 of which showed induction of trimethylation at Lys9 of histone H3 (H3K9me3). In the presence of these epigenetic modifications, enrichment of genes involved in hematopoietic differentiation and in specific signaling pathways was observed; this was associated with an 'inactive' chromatin status, so AML1-ETO binding correlates with changes in the histone modification pattern and increased association of HDACs [47]. On the other hand, AML1-ETO can interact, via its Nervy homology region (which is involved in oligomerization of ETO), with the histone acetyltransferase p300, which acetylates lysines of histones in its target genes, thus activating gene transcription [48].…”
Section: Aml1-eto/t(8;21)mentioning
confidence: 99%
“…To evaluate this hypothesis and the putative leukemic role of the RUNX1 abrogation in the context of our patient, we decided to explore the level of expression of some other genes that had previously been found to be down-regulated by the presence of the RUNX1/ETO fusion. 6 In detail, we used quantitative real-time RT-PCR to study the expression of 4 genes (YES1, MLLT3, CTCF and MAPK1) and we observed a significant downregulation in all of them, both in our patient and in Kasumi-1 ( Figure 1D). Taken together, we observed that these 5 genes, which are undoubtedly involved in cell differentiation, are significantly down-regulated, indicating that the abrogation of RUNX1 observed in our patient results in the loss of its capacity to transactivate RUNX1 target genes, mimicking what has been observed in the presence of the RUNX1/ETO fusion protein.…”
Section: Resultsmentioning
confidence: 99%
“…The calibrated normalized relative quantity, taking into account targetand run-specific amplification efficiencies, was calculated using endogenous GAPDH expression with the Qbase software application. The same approach was used to explore the level of expression of some other genes that were previously found down-regulated by the presence of the RUNX1/ETO fusion (YES1, MLLT3, CTCF and MAPK1), 6 both in our patient and in Kasumi-1 (a cell line carrying the RUNX1/ETO fusion gene).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…We previously reported relatively low SP1 mRNA levels in human haematopoetic stem progenitor cells expressing RUNX1-RUNX1T1 (referred to hereafter as HSPC-RR) and the SKNO1 cell line compared with HSPC (selected CD34 + cells with an empty vector transduction) (Maiques-Diaz et al, 2012). However, abundant SP1 protein levels were observed in RUNX1-RUNX1T1 -expressing cells compared with normal HSPC (Fig 1A).…”
mentioning
confidence: 91%
“…Several studies have reinforced the importance of the interaction between RUNX1-RUNX1T1 and other transcription factors on its DNA-binding profile, and we previously identified the Sp1 transcription factor (SP1) binding site in more than 50% of DNA-bound RUNX1-RUNX1T1 protein (Maiques-Diaz et al, 2012). SP1 induces the expression of essential haematopoietic genes (i.e.…”
mentioning
confidence: 99%